Sexual Orientation Disparities in Papanicolaou Test Use Among US Women: The Role of Sexual and Reproductive Health Services - Agénor, Madina (American Public Health Association, 2014)
We investigated sexual orientation disparities in Papanicolaou screening among US women aged 21 to 44 years (n = 9581) in the 2006 to 2010 National Survey of Family Growth. The odds ratios for lesbian versus heterosexual women and women with no versus only male sexual partners were 0.40 and 0.32, respectively, and were attenuated after adjustment for sexual and reproductive health (SRH) care indicators. Administering Papanicolaou tests through mechanisms other than SRH services would promote cervical cancer screening among all women.